An analysis of the entrepreneurial competencies of the owners/managers of emerging small contractor companies in the construction industry - Makhura, Selaelo Michael (My University, 2012)
This research investigated the entrepreneurial competencies of the owners/managers of 26 emerging small contractors in the construction industry during the period November/December 2010. The study was motivated by the perception that there is a high failure rate of emerging contractor companies. The objective was to analyse, discover gaps and compare and contrast entrepreneurial competencies of owners/managers of emerging contractor companies with similar studies. A self-rating questionnaire was administered to the participants. The participants in the research were drawn from two (2) of the nine (9) provinces of the Republic of South Africa, namely Gauteng and Limpopo Province. The study has demonstrated that owners/managers of the emerging small contractors have both strengths and weaknesses. On the downside the study has shown that the owners/managers of emerging small contractors need support to build opportunity scanning, initiative, persuasion, assertiveness, self-confidence, systematic planning and problem-solving competencies. On the upside the study showed that the owners/managers of emerging small contractors possess persistence, information-seeking, concern for high quality of work, commitment to work contract, use of influence strategies and efficiency orientation competencies. The results of the current study concur with those of Man & Lau (2000) on the centrality of opportunity scanning, commitment and strategic competencies. The differences were found in terms of relationship, organizing and conceptual competencies. The current study differed with Spencer and Spencer (1993) in relation to persistence, information gathering and use of influence strategies. The main lesson is that there is a need to focus on entrepreneurial competencies. This should be in addition to the development of managerial and technical competencies.